2016
DOI: 10.1007/s11306-016-1081-y
|View full text |Cite
|
Sign up to set email alerts
|

Inaccurate quantitation of palmitate in metabolomics and isotope tracer studies due to plastics

Abstract: Introduction Palmitate, the typical end product released from fatty acid synthase, is of interest to many researchers performing metabolomics. Although palmitate can be readily detected by using mass spectrometry, many metabolomic platforms involve the use of plastic consumables that introduce a competing background signal of palmitate. Objectives The goal of this study was to quantify palmitate contamination in metabolomics and isotope tracer studies and to examine the reliability of approaches for reducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…Insulin-secreting MIN6 cells (24) (passage [25][26][27][28][29][30][31][32][33][34][35][36] were cultured at 37°C and 8% CO 2 in a humidified atmosphere. MIN6 cells were grown in DMEM containing 4.5 g/L glucose, supplemented with 15% FBS and 70 mmol/L b-mercaptoethanol (PAN Biotech, Aidenbach, Germany).…”
Section: Tissue Culturementioning
confidence: 99%
“…Insulin-secreting MIN6 cells (24) (passage [25][26][27][28][29][30][31][32][33][34][35][36] were cultured at 37°C and 8% CO 2 in a humidified atmosphere. MIN6 cells were grown in DMEM containing 4.5 g/L glucose, supplemented with 15% FBS and 70 mmol/L b-mercaptoethanol (PAN Biotech, Aidenbach, Germany).…”
Section: Tissue Culturementioning
confidence: 99%
“…Plasticware should not be used as it is a significant source of contamination [25]. A study has shown that fatty acid contamination from plasticware can be inconsistent even within batches and therefore background subtraction may not accurately remove contributions from plasticware [26]. The glassware used should be cleaned with MS-grade solvents and ideally combusted using a high temperature oven (e.g., 400 °C, 4 h).…”
Section: Discussionmentioning
confidence: 99%
“…Food samples are frequently nonhomogenous, and in order to minimize lipid (and phospholipid) degradation, they have to be stored at low temperatures (–20, –80°C, or even in liquid nitrogen). External contamination coming from slip agents, lubricants, or other lipid‐containing ingredients is frequently overseen, but it can cause residual fatty acid contamination during sample preparation . Direct infusion of lipid samples into a mass spectrometer or into an LC system hyphenated with a high‐resolution mass spectrometer (also with multidimensional MS for determination of different species and subclasses), also known as shotgun lipidomics, is frequently used for lipid analysis .…”
Section: Sample Preparation In Metabolomicsmentioning
confidence: 99%
“…External contamination coming from slip agents, lubricants, or other lipid‐containing ingredients is frequently overseen, but it can cause residual fatty acid contamination during sample preparation . Direct infusion of lipid samples into a mass spectrometer or into an LC system hyphenated with a high‐resolution mass spectrometer (also with multidimensional MS for determination of different species and subclasses), also known as shotgun lipidomics, is frequently used for lipid analysis . LC is used as a method for lipid separation, and can be sometimes considered as sample preparation specific for lipidomic analyses.…”
Section: Sample Preparation In Metabolomicsmentioning
confidence: 99%